ANALISIS KORELASI STATUS SPIRITUALITAS DENGAN RESILIENSI PERAWAT RUANG RAWAT INAP DI RS X JAKARTA PUSAT - Tibo, Yuliana Larisa Maria Yohanesa; Utami, Lucia; Prabawati, Dewi (Yayasan Healing and Healthcare Education, 2024)
Nursing services as an integral part of healthcare services contribute significantly to determining the quality of care in hospitals. One factor that can influence resilience is spirituality. The aspect of spirituality can help an individual find meaning in life and accept their conditions, thereby providing a positive response to changes occurring within the individual. The method used in this study is quantitative, with a descriptive correlational research design using a cross-sectional approach. The sample consisted of 91 nurses selected through simple random sampling. The research instruments used were the DSES questionnaire and the Resilience Scale. Results: The majority of nurses had high spiritual status, with 75 nurses (82.4%), and high resilience, with 46 nurses (50.5%). The Kendall Tau C correlation test results showed a p-value of 0.017 (p < 0.05), indicating a significant relationship between spiritual status and nurse resilience. It can be concluded that nurses with high spiritual status will also have high resilience. It is recommended for nurses to continually develop their spiritual lives to maintain good resilience.